ASSESSMENT OF PERFORMANCE FUNCTIONING OF THE PERSONNEL MANAGEMENT SYSTEM AT THE EURASIAN NATIONAL UNIVERSITY NAMED AFTER L.N. GUMILOV (Journal of Economic Research & Business Administration, 2017)
At the present stage structural changes in economy and rapid development of science and technology led to increase of a human factor role in production and management. It is quite natural that at each entity there is a necessity for determination of number of personnel, for effective system of matching, hiring and placement of personnel, for providing their occupation inclusive of production interests and the worker`s interests ,in system of compensation for work, in considering of individual problems of workers, improvement of their social conditions and vacation. Improving the efficiency of personnel management can be achieved by using the following factors: improvement of labor organization; involving personnel in process control; training and development of staff through systematic training and improvement of qualification of workers. When assessing the effectiveness of the personnel management system at the enterprise and analyzing the functions of the personnel management service, it is necessary to conduct a functional and cost analysis of the work activity of individual managers, functional divisions, the organization as a whole and on this basis, develop a set of proposals for its improvement. Through functional and cost analysis, the functions that are unnecessary and unusual to the service of the staff are revealed as well as functions that are not currently performed by personnel. There are no necessary functional interrelationships between the staff service and other functional departments of the organization in terms of functions: to form the organizational structure of the personnel service, to develop personnel policy and personnel management strategy, to carry out personnel planning, to manage motivation and stimulation of personnel, to manage social development, to organize training, retraining and further training personnel. Thus, it is necessary to develop and implement measures to improve the quality of the functions of organizing training, retraining and improving the skills of personnel, managing the career, managing social and industrial conflicts, and making changes to the provision for material incentives.